Implementasi Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar IPAS Peserta Didik Kelas 5 SDN 10 Surau Gadang - Fahira Maiza; Sry Apfani; Rahmia Tulljanah; Riri Marfilinda; Winda Noprina (Journal on Education, 2024)
The issue in this research is that teachers are still using conventional methods, resulting in students not being able to demonstrate active participation and creativity in thinking and acting during IPAS (Science and Social Studies) lessons. This phenomenon is caused by teacher-centered learning, which leads to the majority of students having relatively low academic achievement. Based on this problem, the researcher attempted to implement the Problem-Based Learning (PBL) model. This research aims to assess the planning, implementation, observation, and reflection of problem-based learning in IPAS lessons to improve the academic skills of fifth-grade students at SDN 10 Surau Gadang. The approach used in this research is both qualitative and quantitative. The type of research is classroom action research, conducted in two cycles. The results of the research show a 30% improvement in students' academic performance in the second cycle compared to the first cycle. There was also an increase in the actions and activities of both teachers and students in the second cycle compared to the first cycle. Additionally, students expressed a preference for the problem-based learning model as it helped enhance their academic performance.